RETRACTED ARTICLE: An agent architecture for autonomous UAV flight control in object classification and recognition missions (Soft Computing, (2023), 27, 1, (391-404), 10.1007/s00500-021-05613-8) - Mostafa S.A.; Mustapha A.; Gunasekaran S.S.; Ahmad M.S.; Mohammed M.A.; Parwekar P.; Kadry S. (Springer Science and Business Media Deutschland GmbH, 2025)
The publisher has retracted this article in agreement with the Editor-in-Chief. The article was submitted to be part of a guest-edited issue. An investigation by the publisher found a number of articles, including this one, with a number of concerns, including but not limited to compromised editorial handling and peer review process, inappropriate or irrelevant references or not being in scope of the journal or guest-edited issue. Based on the investigation?s findings the publisher no longer has confidence in the results and conclusions of this article. Authors Mazin Abed Mohammed and Salama A. Mostafa disagree with this retraction. The Publisher has not been able to obtain a current email address for authors Mohd Sharifuddin Ahmad and Pritee Parwekar. Authors Aida Mustapha, Saraswathy Shamini Gunasekaran, Seifedine Kadry have not responded to correspondence regarding this retraction. ? The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature 2024.